(untitled) (Journal of Guidance and Counselling Studies, 2025)
This study investigated the relationship between self-esteem and academic achievement secondary school students in Edo State. Five research questions guided the study, and two null hypotheses was tested at 0.05 level of significance. Correlation research design was adopted for the study. The population for this study consisted of 20,098 senior secondary school (SS2) students. The sample of the study consisted of 2,040 students drawn through multi-stage sampling procedure. The instrument used for the study were Hare Self-esteem Scale (HSS) with a reliability coefficient alpha of 0.83. Descriptive statistics and Pearson Product Moment Correlation were used for data analysis. Results obtained from the study showed that majority of the students in Edo state have high self-esteem. The results also showed that most of the students have high academic achievement in English language and mathematics. Moreso, the result revealed a high positive significant relationship between students’ self-esteem and their academic achievement in English language and Mathematics respectively. The study concluded, among others that secondary school students’ self-esteem is highly related to their academic achievement in English language and Mathematics. It was recommended, among others that counsellors should provide both group and individual counselling services to boost students’ self-esteem. This will help the students to feel worthy and capable of achieving higher academic success through diligence and personal effort.